Novel Endorna-like viruses, including three with two open reading frames, challenge the membership criteria and taxonomy of the Endornaviridae - Ong, J.; Li, H.; Sivasithamparam, K.; Dixon, Kingsley; Jones, M.; Wylie, S. (Reed Elsevier, 2016)
Viruses associated with wild orchids and their mycorrhizal fungi are poorly studied. Using a shotgun sequencing approach, we identified eight novel endornavirus-like genome sequences from isolates of Ceratobasidium fungi isolated from pelotons within root cortical cells of wild indigenous orchid species Microtis media, Pterostylis sanguinea and an undetermined species of Pterostylis in Western Australia. They represent the first endornaviruses to be described from orchid mycorrhizal fungi and from the Australian continent. Five of the novel endornaviruses were detected from one Ceratobasidium isolate collected from one Pterostylis plant. The partial and complete viral replicases shared low (9–30%) identities with one another and with endornaviruses described from elsewhere. Four had genome lengths greater than those of previously described endornaviruses, two resembled ascomycete-infecting endornaviruses, and unlike currently described endornaviruses, three had two open reading frames. The unusual features of these new viruses challenge current taxonomic criteria for membership of the family Endornaviridae.